Precision polymer particles by flash nanoprecipitation and microfluidic droplet extraction - Sharratt,WN; Lee,VE; Priestley,RD; Cabral,JT (ACS Applied Polymer Materials, 2021)
We comparatively review two versatile approaches employed in the precise formation of polymer particles, with length scales from 10s of nm to to 100s μm, from ternary polymer(s), solvent and nonsolvent mixtures. Flash nanoprecipitation (FNP) utilizes an opposing jet arrangement to mix a dilute polymer solution and a nonsolvent in confinement, inducing a rapid (∼millisecond) chain collapse and eventual precipitation of nanoparticles (NPs) of 10–1000 nm diameters. FNP of polymer mixtures and block copolymers can yield a range of multiphase morphologies with various functionalities. While droplet solvent extraction (DSE) also involves the exposure of a polymer solution to a nonsolvent, in this case the polymer solution is templated into a droplet prior to solvent extraction, often using microfluidics, resulting in polymer particles of 1–1000 μm diameter. Droplet shrinkage and solvent exchange are generally accompanied by a series of processes including demixing, coarsening, phase inversion, skin formation, and kinetic arrest, which lead to a plethora of possible internal and external particle morphologies. In the absence of external flow fields, DSE corresponds effectively to nonsolvent induced phase separation (NIPS) in a spherical geometry. In this review, we discuss the requirements to implement both approaches, detailing consequences of ternary solution phase behavior and the interplay of the various processes underpinning particle formation and highlighting the similarities, differences, and complementarity of FNP and DSE. In addition to reviewing previous work in the field, we report comparative experimental results on the formation of polystyrene particles by both approaches, emphasizing the importance of solution phase behavior in process design.